Cutaneous nocardiosis in dogs and cats: Review - De Carvalho Lima Gondim , Adriana; Araujo, Adjanna Karla Leite (Pubvet, 2020)
Dermatopathies represent a large part of the cases seen at the small animal medical clinic. Among skin diseases, bacterial diseases are among the most frequent in dermatological practice. The genus Nocardia consists of aerobic, gram-positive, highly pathogenic bacteria for animals and humans, normally found in soil, water, and other places. Currently, nocardiosis has been considered an emerging disease among humans and domestic animals worldwide. Infection occurs through inhalation of aerosols and contact with the contaminated environment or by percutaneous inoculation of the agent through wounds or trauma, causing, respectively, the clinical respiratory and cutaneous (most common) forms of the disease. The aim of this paper is to make a bibliographic review about nocardiosis in dogs and cats, alerting the veterinarian about the occurrence of such condition.
Keywords: dermatology; bacterial diseases; dog; cat; nocardiosis; Nocardia spp.